Trans-Scaphoid Lunate Fracture Dislocation: A Case Report of a Rare Injury - Younes, Sanad; Saad, Ahmad; Buahlaika , Zeyad (AlQalam Journal of Medical and Applied Sciences, 2024)
Trans-scaphoid lunate dislocation is an uncommon injury but can be devastating, causing loss of wrist joint movement and function, and compromising grip strength. In this report, we present a case of a 48-year-old man with a history of psychiatric disorder who attempted suicide by jumping from the second floor. He sustained a volar lunate dislocation and scaphoid fracture, with migration of the proximal part of the scaphoid to the volar aspect of the forearm. Open surgical reduction was planned through a dorsal approach: first, the lunate was reduced, then the proximal part of the scaphoid was retrieved from the volar aspect of the forearm and anatomically fixed with a 2.5 mm headless screw. The scapholunate relationship was reduced and fixed with two wires through the scapholunate and scaphocapitate joints. The wound was closed in layers, and the wrist joint was immobilized with a dorsal splint for six weeks. Six weeks postoperatively, the K wires were removed, and the patient started physiotherapy. At three months postoperative follow-up, the wrist joint function was good, with good grip strength and a good range of motion. The gold standard treatment option is open reduction and fixation of the fractured bone and stabilization of the carpal bones in anatomical alignment to reduce possible complications such as median nerve compression, chronic carpal instability, chronic wrist pain, loss of grip strength, wrist arthritis, and carpal collapse. خلع العظم الهلالي عبر الزورقي هو إصابة غير شائعة ولكنها قد تكون ذات مضاعفات كبيرة، مما يتسبب في فقدان حركة مفصل الرسغ ووظيفته، ويضعف قوة القبضة. في هذا التقرير، نقدم حالة رجل يبلغ من العمر 48 عامًا ولديه تاريخ من الاضطراب النفسي حاول الانتحار بالقفز من الطابق الثاني. أصيب بخلع هلالي في الزورقي وكسر في الزورقي، مع انتقال الجزء القريب من العظم الزورقي إلى الساعد. تم التخطيط الجراحي المفتوح من خلال نهج ظهري: أولاً، تم ارجاع العظم الهلالي، ثم تم استرداد الجزء القريب من الزورقي من الساعد وتثبيته تشريحيًا بمسمار بدون رأس مقاس 2.5 مم. تم ارجاع العلاقة الزورقية الهلالية وتثبيتها بسلكين من خلال الجلد، تم غلق الجرح على شكل طبقات، وتم تثبيت مفصل الرسغ بجبيرة ظهرية لمدة ستة أسابيع. بعد ستة أسابيع من الجراحة، تمت إزالة الأسلاك ، وبدأ المريض العلاج الفيزيائي. بعد ثلاثة أشهر من المتابعة بعد الجراحة، كانت وظيفة مفصل الرسغ جيدة، مع قوة قبضة جيدة ونطاق جيد من الحركة